1996
DOI: 10.1074/jbc.271.10.5663
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Fibroblast Growth Factor (FGF) Receptor-1 mRNA and Protein by Two Molecular Forms of Basic FGF

Abstract: To evaluate possible functional differences between basic fibroblast growth factor (FGF) 2 isoforms we analyzed the effects of the 18-kDa FGF-2 which mainly localizes in the cytosol and that of the nuclear-targeted 22.5-kDa form on FGF receptors (FGFR) expression. These peptides were expressed at low amounts through a retroviral-infection system. Point mutated FGF-2 cDNAs under the control of the ␤-actin promoter were used to infect a pancreatic cell line (AR4 -2J) which does not produce FGF-2. Saturation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…This suggests that, FGFR1 activation mediated by an autocrine/paracrine loop was the mechanism involved in reducing apoptosis in late passage cells because aged cells accumulated and secreted a higher amount of FGF1 and because inactivation of FGFR1 resulted in an increase in PCD. This is consistent with previous data showing that autocrine stimulation of growth factor receptors makes it possible for cells to resist PCD (39), whereas lower levels of FGFR1 signal transduction are involved in the inability of senescent endothelial cells to respond to exogenous FGF1 (40). mission of the FGF1 signal in RPE cells (28), JNK1 is implicated in the induction of apoptosis after growth factor deprivation (43), and ERK2 and JNK1 have opposing effects on cell death (44).…”
Section: Erk2 Activation and Synthesis In Aged Rpe Cellssupporting
confidence: 91%
“…This suggests that, FGFR1 activation mediated by an autocrine/paracrine loop was the mechanism involved in reducing apoptosis in late passage cells because aged cells accumulated and secreted a higher amount of FGF1 and because inactivation of FGFR1 resulted in an increase in PCD. This is consistent with previous data showing that autocrine stimulation of growth factor receptors makes it possible for cells to resist PCD (39), whereas lower levels of FGFR1 signal transduction are involved in the inability of senescent endothelial cells to respond to exogenous FGF1 (40). mission of the FGF1 signal in RPE cells (28), JNK1 is implicated in the induction of apoptosis after growth factor deprivation (43), and ERK2 and JNK1 have opposing effects on cell death (44).…”
Section: Erk2 Activation and Synthesis In Aged Rpe Cellssupporting
confidence: 91%
“…The molecular basis for this downregulation could be indirect, such as through sequestration of endogenous bFGF. Previous studies showed upregulated cell surface expression of FGFR1 in pancreatic cell lines engineered to express low levels of the cytosolic 18 kDa, or nuclear targeted 22.5 kDa FGF2 isoforms, presumably by increasing the stability of FGFR1 gene transcript (Estival et al, 1996). It is thus possible that the reverse is also true, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The different molecular weight forms of bFGF also show functional differences on FGF receptor function. It was reported that the 22.5-kDa isoform of the bFGF acts by increasing FGF receptor type 1 messenger RNA stability, thus enhancing cell responses to exogenous bFGF (73). It has been postulated that intracellular bFGF is released by alternative mechanisms (18).…”
Section: A B C D E F G Hmentioning
confidence: 99%